Proclaiming and Embodying Peace in Pacifist Japan: a Reformed Church Perspective - Van der Watt, Stéphan (Ecclesial Futures, 2024)
This article assesses a significant Peace Declaration which was recently released by the Reformed Church in Japan (RCJ). Through this declaration the RCJ affirms her calling and responsibility—as a missional church which is part of a 1% Christian population—to proclaim and embody peace in Japan and beyond. The article uses an integrative literature review and in-depth theological reflection as its main research techniques. The systematic review addresses the question: What is the significance and meaning of the RCJ Peace Declaration within the wider field of Peace Studies and in connection with the notion of pacifism in Japan and globally? It is argued that theological understandings of peacebuilding can indeed constructively promote peace and justice in worldwide conflicts. The article further explainshow a vast corpus of knowledge and practice includes the body of Christ in Japan which, through the RCJ Peace Declaration, represents a pro-active vision of God’s shalom. Public witness is not an add-on to the church’s mission. Instead, the Church realizes its missional calling when it publicly engages in testifying to true Christian peace by rejecting imperial claims.